PENERAPAN METODE INDEX CARD MATCH DALAM PENINGKATAN PEMBELAJARAN BILANGAN ROMAWI SISWA KELAS IV SDN 2 WONOREJO KECAMATAN KARANGANYAR TAHUN 2012/2013 - SUPRIHATIN, ENI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Aplication Of The Index Card Match Methods in Improving Learning Roman Numbers IV Grade of Elementary School 2 Wonorejo Karanganyar District in 2012/2013. This research aimed to: describe the application Of The Index Card Match Methods, describe the process of learning roman numbers. The research was conducted in three cycles. Subject of this study is the IV graders of Elementary School 2 Wonorejo, which has 12 students. Data sources came from teachers, students and researchers. Data collection techniques using observation, documentation and testing. The validity of data using triangulation techniques and triangulation of sources. Analysis of the data used by the qualitative and quantitative analysis. The result showed that the application of Index Card Match method can enhance learning in the IV grade of Elementary School 2 Wonorejo. Keywords: Index Card Match, Improving Learning, Roman Numbers. Abstrak: Penerapan Metode Index Card Match dalam Peningkatan Pembelajaran Bilangan Romawi Siswa Kelas IV SDN 2 Wonorejo Kecamatan Karanganyar Tahun 2012/2013. Penelitian ini bertujuan : mendeskripsikan penerapan metode Index Card Match, mendeskripsikan pembelajaran bilangan romawi. Penelitian ini dilaksanakan dalam tiga siklus. Subjek penelitian in adalah seluruh siswa kelas IV SDN 2 Wonorejo yang berjumlah 12 siswa. Sumber data berasal dari siswa, teman sejawat dan peneliti. Teknik pengumpulan data menggunakan observasi, doukmentasi, dan tes. Validitas data menggunakan triangulasi teknik dan triangulasi sumber. Analisis data yang digunakan dengan analsis kualitatif dan kuantitatif. Hasilnya menunjukkan bahwa penerapan metode Index Card Match dapat meningkatkan pembelajaran bilangan romawi di kelas IV SDN 2 Wonorejo. Kata Kunci: Index Card Match, Peningkatan Pembelajaran, Bilangan Romawi